An appraisal of the production and utility of digital atlases in Africa: a case study of Swaziland - Pettit, Louise Manda (Rhodes University, Faculty of Science, Department of Geography, 2000)
This research will appraise the production and utility of digital atlases in an African context, using personal experience gained through the production of a digital atlas for Swaziland, the opinions obtained from other producers of African digital atlases and relevant literature. Since the 1950s, decision makers and researchers have viewed information as a powerful contributor to national development. Over the past thirty years, developed countries have increased the efficient collation and dissemination of geographic information through the utilization of the digital environment. The development of Geographic Information Systems (GIS) has increased the range of applications attainable in digital mapping projects. Applications have ranged from resource inventories to the monitoring of environmental degradation, crime patterns and service provision. The patchy history of data collection, analysis and mapping in Africa, has had a limiting effect on the ability of countries to identify, plan and control their resources efficiently. Despite the desire to automate the mapping process and reap some of the planning benefits evident in the developed world, Africa has not succeeded in mobilising full technological potential. Political instability, poor infrastructure, the absence of national policy guidelines, and a lack of skilled manpower are some of the issues which have limited utilization. Despite many of the hurdles faced by African countries, automated mapping and analysis technologies are still being pursued. The role of computers in the utilisation of data has become apparent through several means, one of which is the digital atlas. Analytical functions in many of these products allow situation modelling and provide superior graphic displays in comparison to their paper counterparts. Several African countries have embarked on the development of national digital databases and in some cases have produced digital national atlases. The potential to improve resource utilization, service provision and land use planning using these atlases, does exist. The production and utility of these atlases in an African context, however, needs closer assessment. "Computers don't clothe, don't cure, don't feed. Their power begins and ends with information. Their usefulness is therefore strictly linked to the ffectiveness of the information" (Gardner,1993:16).
Keywords: Swaziland Atlases; Digital mapping; Geographic information systems; Cartography -- Data processing; Cartography -- Africa